Distribution calculation of magnetic field detection devices induction ferromagnetic bodies - Bogatyrev, J.; Gulevsky, V. (Energy and Automation, 2015)
The influence of gender in the ferromagnetic body on the overall distribution of the magnetic field induction type detection device, taking into account the heterogeneity of its magnetic field with further experimental confirmation of the results.